OPTIMASI STRATEGI TOOLPATH CNC DENGAN GREY RELATIONAL ANALYSIS UNTUK MENINGKATKAN EFISIENSI PEMESINAN - Sihmaulana Dwianto; Genarsih, Tunjung; Syaifur Rohman, Ardianto (J-ENSITEC, 2025)
This study aims to optimize CNC toolpath strategies using Grey Relational Analysis (GRA) to enhance machining efficiency. Five toolpath strategies—Zigzag, Constant Overlap Spiral, Parallel Spiral, One Way, and True Spiral—are systematically evaluated based on spindle speed, feed rate, depth of cut, and step over, assessing their impact on machining performance.The machining process is conducted using a 3-axis CNC milling machine equipped with a 10 mm diameter endmill tool. Data collection is performed through Mastercam software, where numerical simulations precede the application of Grey Relational Coefficient (GRC) and Grey Relational Grade (GRG) computations to determine the optimal toolpath strategy.The results indicate that the Zigzag toolpath, configured with a spindle speed of 1300 RPM, feed rate of 700 mm/min, depth of cut of 0.8 mm, and step over of 8 mm, achieves the highest GRG value, signifying superior machining efficiency. Further analysis demonstrates that optimizing toolpath parameters significantly enhances process stability, reduces energy consumption, and shortens production cycle time, contributing to increased productivity in CNC machining operations. These findings provide valuable insights for the manufacturing industry, presenting a data-driven framework for selecting optimal toolpath strategies to improve machining precision, operational cost efficiency, and sustainable production practices.